2013
DOI: 10.1159/000354854
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Survival of Esophageal Cancer Patients Treated at the Cancer Institute of Iran

Abstract: Introduction: Little data is available on the prognosis of esophageal cancer (EC) in Iran. We studied the short- and long-term survival of EC patients treated at the Cancer Institute of Iran. Methods: 619 patients were followed who had been operated in the years 1997-2006. The 1-month to 5-year survival rates of EC and hazard ratios (HR) for different prognostic factors were estimated. Results: Median survival was 11.5 months and 5-year survival was 10%. Patients at the advanced stage had a 2.1-fold higher ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
6
8
0
Order By: Relevance
“…Similarly, a median survival time of 8.5 months was reported in a nation-wide study from Iran (Harirchi et al, 2014). Mir et al (2013) reported a median survival of 11.5 months and a 5-year survival rate of 10% for EC patients from Tehran, Iran. In a recent systematic review on 18 studies from Iran, the 1-and 5-year survival rates of EC were estimated at 47% and 12% respectively (Yarhusseini et al, 2014).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Similarly, a median survival time of 8.5 months was reported in a nation-wide study from Iran (Harirchi et al, 2014). Mir et al (2013) reported a median survival of 11.5 months and a 5-year survival rate of 10% for EC patients from Tehran, Iran. In a recent systematic review on 18 studies from Iran, the 1-and 5-year survival rates of EC were estimated at 47% and 12% respectively (Yarhusseini et al, 2014).…”
Section: Discussionsupporting
confidence: 53%
“…Samadi et al (2007) reported a median survival of 9 months for EC patients from North-West of Iran. Mir et al (2013) reported a median survival of 11.5 months and a 5-year survival rate of 10% for EC patients from Tehran, Iran. Mir et al (2013) reported a median survival of 11.5 months and a 5-year survival rate of 10% for EC patients from Tehran, Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Another study from Cancer Institute of Iran 26 showed very similar characteristics to the recruited patients 27 ;i.e. similar stage (10% in early stage), gender proportion (45–50% Female) and age.…”
Section: Discussionmentioning
confidence: 55%
“…Another study from Cancer Institute of Iran 26 showed very similar characteristics to the recruited patients 27 ; that is, similar stage (10% in early stage), gender proportion (45-50% Female) and age. Although there is no direct data available to compare recruited subjects to those who did not visit clinic, due to homogenous population and similar socioeconomic conditions, in addition to indirect evidences from cancer registrybased study, 26 it is improbable that nonrecruited cases would markedly different form recruited subjects. Additionally, as controls were matched geographically, they would follow same referral pattern in case of developing symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Most survival rates reported in the literature are static, being calculated from the day of diagnosis or surgery. However, the risk of death changes with time after surgery.…”
Section: Introductionmentioning
confidence: 99%